Kinetics of MCM-41 synthesis under nonagitated and agitated conditions - Kumar D.; Tiwari P.N.; Ahuja P. (My University, 2025)
MCM-41 has been synthesized under both agitated and nonagitated conditions. The optimum conditions of MCM-41 synthesis and the effect of various ions on the crystal yield and synthesis time have been studied. The parameters have been reported in molar ratios to make the studies usable during scale-up. The kinetics of MCM-41 synthesis has been studied under both nonagitated and agitated conditions, and the activation energy and preexponential factor have been determined. The kinetics was found to be first order. The crystal growth rate is found to increase linearly, and the total synthesis time decreases linearly with the Si/CTAB molar ratio for all temperatures. The total time of MCM-41 synthesis under agitated conditions is found to be about one-third, with only a minor decrease in the crystal yield. The acidity of the samples synthesized under agitated conditions is found to be higher than those synthesized under nonagitated conditions. The minimum surfactant concentration for the formation of MCM-41 is 5 times in agitated as compared to nonagitated conditions.